2019
DOI: 10.3389/fcimb.2019.00252
|View full text |Cite
|
Sign up to set email alerts
|

Thymic Microenvironment Is Modified by Malnutrition and Leishmania infantum Infection

Abstract: Detrimental effects of malnutrition on immune responses to pathogens have long been recognized and it is considered a main risk factor for various infectious diseases, including visceral leishmaniasis (VL). Thymus is a target of both malnutrition and infection, but its role in the immune response to Leishmania infantum in malnourished individuals is barely studied. Because we previously observed thymic atrophy and significant reduction in cellularity and chemokine levels in malnourished … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 75 publications
(126 reference statements)
1
33
0
Order By: Relevance
“…major Western blot; Nano LC–MS/MS; LTQ-OrbitrapVelos MS Infected vs healthy 69 51 2019 [ 41 ] 7 L . infantum Flow Cytometry; ITRAQ; Nano LC–MS/MS Protein Malnourished infected vs well nutritioned un-infected 38 71 2019 [ 43 ] 8 L . infantum ITRAQ; Nano LC–MS/MS Malnourished infected vs well nutritioned un-infected and Well nutritioned infected vs well nutritioned un-infected 35 60 2019 [ 44 ] 9 L .…”
Section: Differentially Modulated Proteins In the Host After mentioning
confidence: 99%
See 4 more Smart Citations
“…major Western blot; Nano LC–MS/MS; LTQ-OrbitrapVelos MS Infected vs healthy 69 51 2019 [ 41 ] 7 L . infantum Flow Cytometry; ITRAQ; Nano LC–MS/MS Protein Malnourished infected vs well nutritioned un-infected 38 71 2019 [ 43 ] 8 L . infantum ITRAQ; Nano LC–MS/MS Malnourished infected vs well nutritioned un-infected and Well nutritioned infected vs well nutritioned un-infected 35 60 2019 [ 44 ] 9 L .…”
Section: Differentially Modulated Proteins In the Host After mentioning
confidence: 99%
“…Overall, the studies by Negrão et al [ 40 , 42 , 41 ] demonstrated the species-specific protein modulation in Leishmania infection as well as differentiated the host response through LPS inoculation and Leishmania infection. To observe the immune response effects of malnutrition in Leishmania infection, Losada-Barragán et al [ 43 , 44 ] conducted the differential proteomic studies involving malnourished mice. In both their studies [ 43 , 44 ], they compared the proteomes of protein-malnourished mice (infected with L. infantum ) and uninfected well-nourished mice.…”
Section: Differentially Modulated Proteins In the Host After mentioning
confidence: 99%
See 3 more Smart Citations